Acceptability of Psychosocial Risks Among Court Translators and Interpreters in Lithuania - Bagdžiūnaitė, Emilė; Maskaliūnienė, Nijolė (Vertimo studijos, 2025)
Research on psychosocial risk factors in Lithuania has increasingly focused on employees’ workplace experiences; however, the well-being of translators and interpreters—particularly those working in Lithuania’s courts—remains underexplored. Interpreting is widely recognized as a high-stress activity (Roziner and Shlesinger 2010), making this group especially relevant for psychosocial risk assessment. Translators, meanwhile, also experience significant occupational stress (Courtney and Phelan 2019). This study investigates psychosocial risks among court translators and interpreters in Lithuania using a survey-based approach. The questionnaire classified risk factors into five domains: work environment, work demands, work organization, work content, and interpersonal relationships. Responses were measured using a five-point Likert scale and analysed through correlation matrices to identify patterns and associations. On this basis, the results are considered reliable. They provide insights into the prevalence and acceptability of psychosocial risks in translation and interpreting contexts, contribute to occupational health research, and help identify aspects requiring improvement to ensure acceptable working conditions for translators and interpreters in Lithuania’s courts.
Keywords: psychosocial risk factor; acceptability of psychosocial risk; court interpreting; translation